Private capital inflows and macroeconomic stability in sub-Saharan African countries - Miyuki Shibata; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2002)
The 1990s have witnessed an increase in private capital inflows to sub-Saharan African (SSA) countries. Such capital flows are viewed as volatile and hence a threat to macroeconomic stability. A sudden reversal of capital inflows was one factor underlying the East Asian crisis of 1997. This paper begins with a brief review of theories of currency crises in the light of the East Asian financial crisis. From this, a number of 'crisis indicators', such as the rate of domestic credit expansion and level of foreign exchange reserves, are identified. The nature of the exchange rate regime is central to managing capital inflows and vulnerability to crisis. The paper then examines trends in exchange rate regimes and crisis indicators for five SSA countries in the 1990s. While there is evidence of increased pressure for real exchange rate appreciation in the 1990s, none of the indicators suggest that managing private flows poses a problem to the economies. One problem that is identified is the prevalence of large trade deficits that could be exacerbated by exchange rate appreciation.
Keywords: 330